Discussion of Data on the Killing by Cold of Fruit Fly Larvae in Mangosteens - T .P. Hutchinson (Agriculture and Natural Resources, 1993)
Burikam et al. have recently quantified the relationship between exposure to cold and death of fruit fly larvae infesting mangosteens. It is shown here that the results are robust with respect to a number of minor changes that could have been made in the statistical analysis. But the results are very sensitive to the choice of statistical model assumed (probit or logit).